IMF/Netherlands Program : Legal and Judicial Report in Indonesia 2000-2004. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The evaluation of the IMF/Netherlands Program for legal and judicial reform in Indonesia was undertaken during July 2004 in Jakarta by a team of three persons appointed by the Government of Indonesia, the Government of the Netherlands, and the IMF. All three are well acquainted with Indonesia and its legal institutions. Together they interviewed over sixty-six persons from twenty-nine institutions and organizations, including IMF and World Bank personnel, judicial personnel, other government officials, private contractors, non-governmental organizations in any way connected with the Program, and foreign donor organizations engaged in relevant programs. The members of the evaluation team and the list of those whom they interviewed can be found in appendixes one and two.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet